Assessment of biopsy proven liver fibrosis by two-dimensional shear wave elastography in patients with primary biliary cholangitis. Issue 5 (May 2020) - Yan, Yuling; Xing, Xian; Lu, Qiang; Wang, Xiaoze; Luo, Xuefeng; Yang, Li
Abstract: Background: Two-dimensional shear-wave elastography (2D-SWE) is an ultrasound-based technique used to stage liver fibrosis by measuring liver stiffness (LS). The diagnostic performance of 2D-SWE for assessing liver fibrosis in patients with primary biliary cholangitis (PBC) has not been reported before. Aims: To investigate the diagnostic performance of 2D-SWE for staging liver fibrosis in patients with PBC by using histologic analysis as a reference standard. Methods: Patients with PBC who underwent liver biopsy and 2D-SWE were retrospectively collected. Liver fibrosis was staged according to the Scheuer scoring system. Areas under receiver operating characteristic curve (AUROC) was constructed to assess the accuracy of 2D-SWE and serum fibrosis models for staging liver fibrosis. Results: The diagnostic performance characteristics were determined for 157 patients with PBC. The AUROCs of LS measured by 2D-SWE for significant fibrosis, severe fibrosis, and cirrhosis were 0.88, 0.97 and 0.99, respectively. The cutoff values of LS measured by 2D-SWE in discriminating significant fibrosis, severe fibrosis, and cirrhosis were 10.7 kPa, 12.2 kPa and 14.1 kPa, respectively. The diagnostic accuracy of 2D-SWE for staging liver fibrosis was 73.9%. Conclusions: 2D-SWE is an efficient noninvasive method for the assessment of liver fibrosis in patients with PBC.